Challenges in providing correctional service education: A case study in a correctional institution in Amhara regional state, Ethiopia - Genet Gelana Kabeta; S G Pretorius (Bahir Dar Journal of Education)
The purpose of this study was to identify the challenges encountered in the provision of correctional service education in a correctional institution in Amhara National Regional State, Ethiopia. Guided by the constructivist paradigm, the study employed qualitative case study as a strategy, involving sixteen participants selected through purposive sampling from one institution. Data collected through one-on-one interviews and focus group discussions were thematically analysed. The study identified long and stringent procedures, inmates’ misbehaviour, lack of resources and facilities, mismatch between inmates’ needs and curricular contents, and lack of monitoring and evaluation as challenges affecting the provision of education. It was concluded that the majority of challenges faced in the case correctional institution occurred as a result of inadequate attention and conflicting missions of the correctional institution (security and rehabilitation) and the tendency of prioritizing security over rehabilitation. In order to mitigate the problems and to improve the provision of correctional service education, possible suggestions are forwarded.